The Efforts to Prevent & Eradicate Criminal Acts of Spreading Fake News and Hate Speech - Bambang Tri Bawono; Gunarto Gunarto; Jawade Hafidz (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The purpose of this study was to identify and analyze efforts to prevent and eradicate the crime of spreading fake news in the community and to identify and analyze law enforcement against Article 28 paragraph (1) of Act No. 19 of 2016 concerning Amendments to Act No. 11 of 2008 concerning Information and Electronic Transactions. Advances in technology have had many impacts on people's lives, including in terms of information and social interaction in society. The absence of boundaries in cyberspace often makes someone less wise in using social media on the internet. One of them can be seen in the issue of spreading fake news. The approach method used in this research is a sociological juridical approach. The results of this study indicate that efforts to prevent criminal acts of spreading fake news can be done through digital literacy and do not share or broadcast in cyberspace, unless the truth is known. Meanwhile, the repressive efforts made by the government against the crime of spreading fake news are the existence of the criminal provisions of Article 28 paragraph (1) of Act No. 19 of 2016 concerning Amendments to Act No. 11 of 2008 concerning Information and Electronic Transactions. The novelty of this study is for law enforcement against the crime of spreading fake news starting from investigation, prosecution, examination of court trials to court decisions.